Pengaruh Content Marketing, Endorsement Influencer, Dan Customer Review Terhadap Minat Beli Keripik Lokal (Studi pada Generasi Z di Kabupaten Mojokerto) - Yanur Rifky Sumazakya; Muhammad Ridwan Basalamah; Ahmad Subhan Mahardani (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the effect of content marketing, influencer endorsement, and customer reviews on purchase intention toward local chips among Generation Z in Mojokerto Regency. This research uses a quantitative approach with a survey method involving 85 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results indicate that content marketing, influencer endorsement, and customer reviews simultaneously and partially have a positive and significant effect on purchase intention toward local chips among Generation Z in Mojokerto Regency. These findings suggest that effective digital marketing strategies, credible influencer endorsements, and informative customer reviews can increase consumers’ interest in purchasing local chip products. Therefore, local chip business owners are encouraged to utilize digital marketing strategies and social media platforms to enhance consumer engagement and improve purchase intention among Generation Z. Keywords: Content Marketing, Influencer Endorsement, Customer Review, Purchase Intention, Generation Z